2022
DOI: 10.2298/fil2217021s
|View full text |Cite
|
Sign up to set email alerts
|

Fixed point and common fixed point theorems on (α,f)-contractive multi-valued mappings in uniform spaces

Abstract: In this paper, we introduce the notion of (?,F)-contractive multi-valued mappings in the setting of uniform spaces. Some fixed point and common fixed point theorems for (?,F)-contractive mappings endowed with the uniform spaces are established. The existence and uniqueness of fixed points by using the structure of uniform spaces is discussed in detail. We set up a non-trivial example for the elaboration of these novel results. eventually, an application is also provided to elaborate the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Klim et al [19] demonstrated FP theorems involving F -contractions for dynamic processes. In 2022, Sagheer et al [20] developed the concept of (↑, F )-contractive multi-valued mappings on uniform spaces and proved certain fixed-point results. In 2010, Basha [21] introduced the notion of the best proximity point (BPP) for nonself mappings on metric spaces, and subsequent research has explored the existence of BPP for non-self mappings on metric spaces (see for example [22,23]).…”
Section: Introductionmentioning
confidence: 99%
“…Klim et al [19] demonstrated FP theorems involving F -contractions for dynamic processes. In 2022, Sagheer et al [20] developed the concept of (↑, F )-contractive multi-valued mappings on uniform spaces and proved certain fixed-point results. In 2010, Basha [21] introduced the notion of the best proximity point (BPP) for nonself mappings on metric spaces, and subsequent research has explored the existence of BPP for non-self mappings on metric spaces (see for example [22,23]).…”
Section: Introductionmentioning
confidence: 99%